The lifecycle of molecular clouds in nearby star-forming disc galaxies - Chevance, Mélanie; Kruijssen, Diederik; Hygate, Alexander P. S.; Schruba, Andreas; Longmore, Steven N; Groves, Brent; Henshaw, Jonathan D.; Herrera, Cinthya N; Hughes, Annie; Jeffreson, Sarah; Lang, Philipp; Leroy, Adam K; et al. (Monthly notices of the Royal Astronomical Society, 2020)
It remains a major challenge to derive a theory of cloud-scale (≲100 pc) star formation and feedback, describing how galaxies convert gas into stars as a function of the galactic environment. Progress has been hampered by a lack of robust empirical constraints on the giant molecular cloud (GMC) lifecycle. We address this problem by systematically applying a new statistical method for measuring the evolutionary timeline of the GMC lifecycle, star formation, and feedback to a sample of nine nearby disc galaxies, observed as part of the PHANGS-ALMA survey. We measure the spatially resolved (∼100 pc) CO-to-H α flux ratio and find a universal de-correlation between molecular gas and young stars on GMC scales, allowing us to quantify the underlying evolutionary timeline. GMC lifetimes are short, typically $10\!-\!30\,{\rm Myr}$, and exhibit environmental variation, between and within galaxies. At kpc-scale molecular gas surface densities ΣH2≥8M⊙pc−2, the GMC lifetime correlates with time-scales for galactic dynamical processes, whereas at ΣH2≤8M⊙pc−2 GMCs decouple from galactic dynamics and live for an internal dynamical time-scale. After a long inert phase without massive star formation traced by H α (75-90 per cent of the cloud lifetime), GMCs disperse within just 1-5 Myr once massive stars emerge. The dispersal is most likely due to early stellar feedback, causing GMCs to achieve integrated star formation efficiencies of 4-10 per cent. These results show that galactic star formation is governed by cloud-scale, environmentally dependent, dynamical processes driving rapid evolutionary cycling. GMCs and H ii regions are the fundamental units undergoing these lifecycles, with mean separations of 100−300 pc in star-forming discs. Future work should characterize the multiscale physics and mass flows driving these lifecycles.
Advance access publication 2019 December 19
Gesehen am 15.04.2021